USE OF ARTIFICIAL INTELLIGENCE TECHNOLOGIES FOR THE QUALIFICATION TRAINING OF MATHEMATICS TEACHERS - Saparov O. (Bright Mind Publishing, 2025)
This article provides a scientific and practical analysis of integrating artificial intelligence (AI) into Uzbekistan's education system. It considers the theoretical and practical bases of AI use, including a 5-stage model and experience of using platforms such as Eduten. The article also pays attention to curriculum development, methodological projects, and the graphical representation of abstract mathematical concepts using AI tools such as ChatGPT, Eduaide.AI, Wolfram, and GeoGebra AI, among others.
Keywords: Mathematics teachers, professional development, artificial intelligence, ChatGPT, Eduaide.AI, GeoGebra AI, pedagogical technologies, curricula, methodological projects, interactive learning.